Supervisi Klinik Model Akademik terhadap Kinerja Perawat Pelaksana - Ika Sulistiawati; Asep Setiawan; Fauziah Rudhiati; Iin Inayah; Murtiningsih Murtiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of clinical supervision with an academic model on the performance of implementing nurses at Sekarwangi Hospital, Sukabumi Regency. The method used in this research uses quantitative research with the type of quasi-experiment research. The results of this study for the unpaired t-test obtained a p-value of 0.000 in the control group. The intervention and unpaired t-test received the p-value in the intervention group were 0.334, and in the control group, the p-value was 0.334. In conclusion, there is a difference in the average performance of the implementing nurse before the supervision of the academic model is carried out. In the intervention group and the control group, there was no difference in the average performance of the implementing nurses after supervision of the academic model between the intervention and control groups, and there was no relationship between the level of education, length of service, motivation, and perceptions with the performance of the implementing nurses. Keywords: Performance of Implementing Nurses, Academic Model Supervision